Characterizing the spin state of an atomic ensemble using the magneto-optical resonance method - Julsgaard, B; Sherson, J; Sørensen, J L; Polzik, E S (Journal of optics. B, Quantum and semiclassical optics, 2004)
Quantum information protocols utilizing atomic ensembles require preparation of a coherent spin state (CSS) of the ensemble as an important starting point. We investigate the magneto-optical resonance method for characterizing a spin state of caesium atoms in a paraffin coated vapour cell. Atoms in a constant magnetic field are subject to an off-resonant laser beam and an RF magnetic field. The spectrum of the Zeeman sub-levels, in particular the weak quadratic Zeeman effect, enables us to measure the spin orientation, the number of atoms, and the transverse spin coherence time. Notably the use of 894 nm pumping light on the D1 line, ensuring the state F = 4, m(F) = 4 is a dark state, helps us to achieve spin orientation of better than 98 percent. Hence we can establish a CSS with high accuracy, which is critical for the analysis of the entangled states of atoms.